Reliability Analysis of Power Supply and Protection Systems Against Electrical Disturbances in Fiber Optic Networks in Lightning-Prone Areas - Kevin Ferdinand Tamba; Dino Erivianto; Zuraidah Tharo (CERED Indonesia Institute, 2025)
Fiber-optic communication networks play a crucial role in ensuring smooth high-speed data transmission. However, in lightning-prone areas, these networks are susceptible to disruptions due to voltage surges and power outages, which can degrade service quality. This study aims to analyze the reliability of the power supply and protection systems used in fiber-optic network infrastructure in lightning-prone areas. The research methods include field surveys, power quality measurements, and evaluation of the lightning protection and grounding system designs used. Data were collected from measurements of voltage, current, and duration of electrical disturbances, as well as interviews with network technicians. The analysis results indicate that most disturbances are caused by voltage surges due to indirect lightning strikes that propagate through the power supply lines. Implementation of a protection system that combines surge arresters, effective grounding, and backup power sources (UPS and generators) has been shown to increase network reliability by up to 92% based on Mean Time Between Failure (MTBF) calculations. This study recommends the implementation of a layered protection system with regular maintenance to minimize the impact of electrical disturbances on fiber-optic networks in lightning-prone areas.